Scaling Up Nutrition in the Democratic Republic of Congo : What Will It Cost? - Shekar, Meera; Mattern, Max; Laviolette, Luc; Dayton Eberwein, Julia; Karamba, Wendy; Akuoku, Jonathan Kweku (World Bank, Washington, DC, 2017)
This paper builds on global experience and the DRC’s specific context to identify an effective nutrition approach along with costs and benefits of key nutrition interventions. It is intended to help guide the selection of the most cost-effective interventions as well as strategies for scaling these up. The paper considers both relevant ‘nutrition-specific’ interventions, largely delivered through the health sector, and multisectoral ‘nutrition-sensitive’ interventions, delivered through other sectors such as agriculture, education, and water and sanitation. The authors estimate that the costs and benefits of implementing 10 nutrition-specific interventions in all provinces of the DRC would require a yearly public investment of $371 million. The expected benefits are enormous: annually over 5.4 million DALYs and over 76,000 lives would be saved, while at least 1 million cases of stunting among children under five would be averted. Economic productivity could potentially increase by $591 million annually over the productive lives of the beneficiaries, with an impressive internal rate of return of 13.6 percent. However, because it is unlikely that the Government of the DRC or its partners will find the $371 million necessary to reach full coverage, authors also consider scale-up scenarios based on considerations of their potential for impact, burden of stunting, resource requirements, and implementation capacity. The most cost-effective scenario considered would provide a subset of key interventions in provinces with the highest rates of stunting and will cost between $97 and $185 million depending on how many provinces are covered. The authors then identify and cost six nutrition-sensitive interventions relevant to the DRC and for which there are both evidence of positive impact on nutrition outcomes and some cost information. These findings point to a powerful set of nutrition-specific interventions and a candidate list of nutrition-sensitive approaches that represent a highly cost-effective approach to reducing child malnutrition in the DRC.